1982
DOI: 10.1136/bmj.285.6343.685
|View full text |Cite
|
Sign up to set email alerts
|

Long-term antihypertensive treatment inhibiting progression of diabetic nephropathy

Abstract: Six men aged 26-35 years with proteinuria due to insulindependent juvenile-onset diabetes were treated for moderate hypertension (mean blood pressure 162/103 mm Hg) and studied for a mean of 73 months for the effect on the progression of nephropathy. All patients were of normal weight. During a mean control period of 28 months before treatment the mean glomerular filtration rate (three or four measurements) was 86-1 ml/ min and mean 24-hour urinary albumin excretion (also three or four measurements) 3 9 g (ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
236
1
9

Year Published

1988
1988
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 728 publications
(261 citation statements)
references
References 16 publications
15
236
1
9
Order By: Relevance
“…Second, Parving et al showed that effective antihypertensive treatment with metoprolol, hydralazin and furosemide could slow the progression of nephropathy [5,40]. The rate of decline in GFR with those drugs (0.37ml.min-a.month -1 [401, 0.22ml.min -1 9 month -t [5], 0.49ml-min-l-month -1 [3]) appears to be comparable to the rate with enalapril (0.40 ml. min-l-month -a [411, 0.20ml-min-l.month -1 [71).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, Parving et al showed that effective antihypertensive treatment with metoprolol, hydralazin and furosemide could slow the progression of nephropathy [5,40]. The rate of decline in GFR with those drugs (0.37ml.min-a.month -1 [401, 0.22ml.min -1 9 month -t [5], 0.49ml-min-l-month -1 [3]) appears to be comparable to the rate with enalapril (0.40 ml. min-l-month -a [411, 0.20ml-min-l.month -1 [71).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is often associated with diabetic nephropathy [2], and effective antihypertensive treatment has proven to be effective in slowing the progression rate of nephropathy [3][4][5]. Recent studies in patients with diabetic nephropathy suggest that the use of angiotensin converting enzyme (ACE) inhibitors may possess specific advantages in decreasing proteinuria and slowing progression of nephropathy [6][7][8][9].…”
mentioning
confidence: 99%
“…Two decades ago, it was demonstrated that antihypertensive treatment could delay the development of end-stage renal failure by reducing the rate of decline of the GFR [21,22], a finding that has subsequently been confirmed in randomised controlled trials (see below). Observational studies indicate a decline in the GFR of 3.7 ml min −1 year −1 in patients on antihypertensive therapy [23].…”
Section: The Changing Course Of Diabetic Kidney Diseasementioning
confidence: 92%
“…Normotensive patients with advanced DN show slower progression compared with hypertensive patients. [33][34][35][36][37][38][39][40][41][42] Non-pharmacologic approaches (dietary modifications especially and increased physical activity) are effective in reducing BP in non-diabetic individuals 43 and may have similar benefits for diabetic patients. However, pharmacologic approaches remain the mainstay for controlling BP in patients with DM.…”
Section: Blood Pressure Controlmentioning
confidence: 99%